2023
DOI: 10.15252/embj.2022112614
|View full text |Cite
|
Sign up to set email alerts
|

YAP/BRD4‐controlled ROR1 promotes tumor‐initiating cells and hyperproliferation in pancreatic cancer

Abstract: Tumor‐initiating cells are major drivers of chemoresistance and attractive targets for cancer therapy, however, their identity in human pancreatic ductal adenocarcinoma (PDAC) and the key molecules underlying their traits remain poorly understood. Here, we show that a cellular subpopulation with partial epithelial‐mesenchymal transition (EMT)‐like signature marked by high expression of receptor tyrosine kinase‐like orphan receptor 1 (ROR1) is the origin of heterogeneous tumor cells in PDAC. We demonstrate that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 88 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…The molecular characterization of various cancers has revealed a considerable degree of intratumoral heterogeneity with distinct cancer cell populations that exhibit genomic and phenotypic diversity [40]. Recent studies have revealed that this applies also to ROR1 and ROR2 as both have been observed to be heterogeneously expressed in pancreatic and mammary tumors in vivo [41][42][43]. Of note, ROR1-high tumor cells were enriched after chemotherapy and displayed a partial EMT-like phenotype with a higher capacity for tumor growth, metastasis formation and therapy resistance compared to ROR1-low tumor cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular characterization of various cancers has revealed a considerable degree of intratumoral heterogeneity with distinct cancer cell populations that exhibit genomic and phenotypic diversity [40]. Recent studies have revealed that this applies also to ROR1 and ROR2 as both have been observed to be heterogeneously expressed in pancreatic and mammary tumors in vivo [41][42][43]. Of note, ROR1-high tumor cells were enriched after chemotherapy and displayed a partial EMT-like phenotype with a higher capacity for tumor growth, metastasis formation and therapy resistance compared to ROR1-low tumor cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…RNA‐sequence analyses of high ROR2‐expressing cells revealed the enrichment of molecules, such as E2F transcription factor 2 (E2F) targets and AURORA KINASES. ROR1, another ROR family molecule, is also heterogeneously expressed in pancreatic cancer tissues, and plays roles in cell proliferation and tumor initiation with AURORA KINASE and the activation of E2F 46 …”
Section: Significance Of Ascl1 In Sclcmentioning
confidence: 99%
“…Clinical studies further indicated that in pancreatic cancer patients, BRD4 (high)/caveolin-2 (high) was associated with shorter disease-free survival. Another study by Yamazaki et al 529 further reported that YAP/BRD4 binding at the enhancer region is associated with transcriptional activation of receptor tyrosine kinase-like orphan receptor 1 (ROR1), thereby promoting tumor growth and metastasis.…”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%